Constellation - Anderson, Sam; Baker, Joe; Blanco, Richard 1968-; Coumans, Hadrien; Smith, Tracy K. 1972-; Torres, Edwin; Yang, Jeffrey 1974- (Princeton Architectural Press, 2015)
"Beginning in June 2015, a new constellation rises nightly above a small island in the middle of the Hudson River, sixty miles north of New York City. Every evening as the sun sets, starry points of light emerge one by one with the stars of the night sky above the Bannerman Castle ruin between Cold Spring and Beacon, NY. Constellation, the book, accompanies this mysterious but sublime installation, both as an extension and artifact of the project. The book is a visual and literary dialogue between artist Melissa McGill and several celebrated writers and poets, using the artwork as a springboard for inspiration and collaboration."